Adsorption of cationic surfactant as a probe of the montmorillonite surface reactivity in the alginate hydrogel composites - Silva Do Nascimento, Danielle (2022)
Adsorption of a cationic surfactant allowed to probe the surface reactivity of montmorillonite encapsulated in a composite of alginate hydrogels (A-MMT). Dodecylbenzyldimethylammonium chloride (BAC-12) was the surfactant used for these studies. BAC-12 is part of the widely used surfactant mixture known as benzalkonium chloride. XRD showed that up to three different types of basal spacing (d001) were present within the composite indicating that as the concentration of adsorbed BAC-12 increases, populations with different adsorption conformational arrangements are present, even unexpanded clay remains. From the SEM-EDS spectra it is observed that the clay is distributed in the whole composite. In addition, the effect of the presence of cationic and anionic biocides on BAC-12 adsorption was studied. Cationic biocides such as tetradecyllbenzyldimethylammonium chlorides (BAC-14) and paraquat (PQ) show a competitive behavior for the clay adsorption sites at BAC-12 low concentration indicating an electrostatic adsorption mechanism. However, the presence of anionic contaminants such as 2,4-D and metsulfuron methyl do not affect surfactant adsorption. In all scenarios is observed an abrupt increase of BAC-12 adsorbed amount reaching values higher than the clay CEC suggesting strong tail-tail interactions. This occurs at concentrations 10 times lower than the CMC of BAC-12 promoted by clay encapsulation in the composite. In these composites the alginate does not affect the surface reactivity of the clay, but the formation of the hydrogel allows it to be easily extracted from aqueous media which makes it an interesting material with a potential use in water remediation.